Crossing the river : a memoir of the American left, the Cold War, and life in East Germany - Grossman, Victor, 1928- (Book collections on Project MUSE., 2003)
Faced with an accusation from the US Army's highest legal authority in 1952, Grossman left his unit stationed in Bavaria and swam the Danube to East Germany. He traces his childhood and experiences as a student, worker, and soldier; then describes life in his new home among a surprisingly large community of defectors. There is no index. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com).